The Determinants of Effective Islam-Based Junior High School in the Regency of Purbalingga - Wahyudhiana, Wahyudhiana; Rokhman, Fathur; Soesanto, Soesanto; Kardoyo, Kardoyo (The Journal of Educational Development, 2018)
This study is based on the performance of education supervisors, the performance of madrasah principals, the performance of professional teachers, and the performance of madrasah committees, which synergize into the model of effective madrasah tsanawiyah in Purbalingga District. The problems raised in this study are (1) whether the relationships among the variables affecting the effectiveness of madrasah can be empirically tested and (2) how the contribution of education supervisors, heads of madrash, professional teachers, and madrasah committees to the quality of madrasah processes and effectiveness. This research was designed as a correlational study using path analysis. The population of this study was all professional teachers in 31 of 39 public and private MTs accredited "A" and "B" in Purbalingga District. The total number of population was 334 people with the error rate of 10%. The sample size was 150 people. The data were analyzed based on the structural equation model (SEM) using AMOS. Based on the data analysis, it was found that: First, there is a correlation between the conceptual model and the empirically tested model. Second, the performance of education supervisor, head of madrasah, professional teacher, and madrasah committee have an effect on the quality process. The contribution of the exogenous variable influence was 89.9%, the rest 10.1% was influenced by other factors beyond the model. Third, the contribution of quality process variable, education supervisor, head of madrasah, professional teacher, and madrasah committee on effective madrasah was 93.4%, the rest 6.6% was influenced by other factors. Fourth, the model can be used to predict effective madrasahs with the effort of managing the tested exogenous variables. It can be recommended that the effective madrasah tsanawiyah model can be used to predict the effectiveness of madrasah by prioritizing on quality process variables, professional teacher performance, madrasah head performance, and madrasah committees performance, with various sciences and insights.